Penerapan Nilai-Nilai Humanistik dalam Pembelajaran Tatanen di Bale Atikan untuk Penguatan Karakter Anak di Kelas V SDN 2 Tanjungsari - Siti Honijah; Dian Mardia; Lilih Nurmilah; Ricky Yoseptry; Arif Firmansyah (STKIP PGRI SITUBONDO, 2025)
Education at the elementary school level plays a strategic role in shaping students’ character as a foundation for future personality development. At the elementary school age, children are in a stage of moral and social development that is strongly influenced by the learning environment, daily interactions, and concrete experiences they encounter at school. Therefore, character education in elementary schools needs to be designed not only through cognitive instruction but also through meaningful, contextual learning experiences that engage students’ affective and psychomotor domains. Humanistic values represent a set of values that place human beings at the center of the educational process. The research methodology used in this study is qualitative research with a case study design. This approach is employed to gain an in-depth understanding of how humanistic values are implemented in Tatanén learning activities at Balé Atikan and how these values contribute to strengthening students’ character. Overall, the findings indicate that Tatanén learning at Bale Atikan in SDN 2 Tanjungsari has effectively served as a medium for implementing humanistic values. Through activities such as farming, caring for the environment, working in groups, engaging in reflection, and making meaning of each process involved, students gain authentic learning experiences that reinforce values of empathy, responsibility, independence, care, cooperation, and respect for life.